Pengaruh Perbandingan Tepung Terigu dan Tepung Jamur Tiram Putih terhadap Sifat Sensori dan Fisik Takoyaki - Siti Yultria; Sussi Astuti; Fibra Nurainy (Universitas Djuanda, 2026)
Substitution for wheat flour in takoyaki products can be done with white oyster mushroom flour. The sensory and physical properties of takoyaki in various ratios of wheat flour and white oyster mushroom flour and determining the best level of comparison are the research objectives. The research was structured as a single factor and four replications in a Complete Randomized Block Design (RAKL). The single factor is six levels of ratio of wheat flour and white oyster mushroom flour, namely 100%:0%; 90%:10% ; 85%:15% ; 80%:20% ; 75%:25% and 70%:30%, analyzed by Anara and 5% BNT test. Treatment P1 (90% wheat flour : 10% white oyster mushroom flour) was the best treatment with a texture score of 7.27 (quite soft), a taste score of 6.47 (quite savory), a color score of 6.33 (yellowish brown), a score of aroma 6.84 (like), overall acceptance score 6.80 (like), and tinkle ratio 3.67%. This treatment contained 59.64% water content, 2.49% crude fiber content, 4.16% protein content, 3.42% fat content, and 28.87% carbohydrate content. The research results show the potential of white oyster mushroom flour as a substitute for wheat flour in making takoyaki.